Troubled Waters: the Taiwan Issue since the Third Taiwan Strait Crisis - Voloshina, Anna (Rethinking Asia in World Politics, 2023)
Over the last seventy years the Taiwan Strait has been widely seen as a place where the next major conflict between the great powers could start. The last time when Asia found itself on the brink of war over the future of the island nation was the Taiwan Strait Crisis of 1995–1996. In this article, the author examines the crisis background, events and consequences and suggests that the confrontation marked the emergence of a new status quo in the strait area, the one of a structural deadlock. This paper provides an analysis of the three subsequent periods (2000–2008, 2008–2016 and since 2016 until the present) in the evolution of that status quo. The author argues that in the recent years the situation in the Taiwan Strait has been shifting towards increased turbulence. The study identifies the major factors that are eroding the “pillars” of the status quo and, thus, have a destabilizing effect on the relations between Beijing, Washington and Taipei. As such factors are of a structural nature the author concludes that the room for maneuver for each side of the triangle is becoming increasingly narrow. It enhances the risk of a structural deadlock escalating into an armed conflict.